On the mechanism of turbulent flow in mass-transfer controlled electrochemical reactions - Arvia, Alejandro Jorge (1964)
The effect of turbulence on the rate of electrochemical reactions under diffusion control is considered. Cylindrical cells with rotating electrodes were employed. Experimental results are interpreted in terms of Wranglén's treatment of turbulence recently given. Accordingly the limiting current density is proportional to the 3/5th power of fluid velocity and to the 1/3rd power of Schmidt number. The dependence of the kinetic constant on viscosity and diffusivity indicates a mechanism of ionic mass transfer based on the penetration of eddies into the laminar sublayers.